PENERAPAN GMP PADA PENANGANAN PASCA PANEN KOPI RAKYAT UNTUK MENURUNKAN OKRATOKSIN PRODUK KOPI (STUDI KASUS DI SIDOMULYO, JEMBER) - Miftahul Choiron (AGROINTEK, 2010)
Jember potential to become one of the world's coffee suppliers. The survey showed that farmers need to add the sorting stage in the processing of coffee to get good quality coffee beans and uniforms. Stages of the process that needs to be improved is the stage of drying and storage. At the stage of drying, need to improve standards of drying up to 12.5% (SNI) as a standard in use today are still high enough to 14%. Water content is still possible to increase especially during storage and hence, potentially causing the growth of Aspergillus ochraceus as a ocratoxin producer. At the storage stage, the coffee must be placed in clean bags and stacked on a wooden base, and does not stick to the wall. This is done to avoid increasing the water content in the coffee because of moisture on the floor and walls. From the analysis of water content is known that an increase in product moisture content of 13.6% to 13.9% during storage.